2020 EACTS/ELSO/STS/AATS Expert Consensus on Post-cardiotomy Extracorporeal Life Support in Adult Patients. Issue 1 (January 2021) - Lorusso, Roberto; Whitman, Glenn; Milojevic, Milan; Raffa, Giuseppe; McMullan, David M.; Boeken, Udo; Haft, Jonathan; Bermudez, Christian A.; Shah, Ashish S.; D'Alessandro, David A.
Abstract : Post-cardiotomy extracorporeal life support (PC-ECLS) in adult patients has been used only rarely but recent data have shown a remarkable increase in its use, almost certainly due to improved technology, ease of management, growing familiarity with its capability and decreased costs. Trends in worldwide in-hospital survival, however, rather than improving, have shown a decline in some experiences, likely due to increased use in more complex, critically ill patients rather than to suboptimal management. Nevertheless, PC-ECLS is proving to be a valuable resource for temporary cardiocirculatory and respiratory support in patients who would otherwise most likely die. Because a comprehensive review of PC-ECLS might be of use for the practitioner, and possibly improve patient management in this setting, the authors have attempted to create a concise, comprehensive and relevant analysis of all aspects related to PC-ECLS, with a particular emphasis on indications, technique, management and avoidance of complications, appraisal of new approaches and ethics, education and training. Abstract : Supplemental Digital Content is available in the text.